2019
DOI: 10.1155/2019/6492029
|View full text |Cite
|
Sign up to set email alerts
|

MHY2233 Attenuates Replicative Cellular Senescence in Human Endothelial Progenitor Cells via SIRT1 Signaling

Abstract: Cardiovascular diseases (CVDs) are a major cause of death worldwide. Due to the prevalence of many side effects and incomplete recovery from pharmacotherapies, stem cell therapy is being targeted for the treatment of CVDs. Among the different types of stem cells, endothelial progenitor cells (EPCs) have great potential. However, cellular replicative senescence decreases the proliferation, migration, and overall function of EPCs. Sirtuin 1 (SIRT1) has been mainly studied in the mammalian aging process. MHY2233 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 55 publications
(71 reference statements)
1
31
0
Order By: Relevance
“…Considering that bone marrows are one of the major sources to provide EPCs and enable EPC homing to injured endothelium [30], we supposed that the lower proliferation and migration of EPCs in CAS group manifested the general conditions of the disease, which was similar to the previous ndings in human being [31,32]. Previous clinical ndings suggested that SIRT1 might be protective in CAS patients and in vitro, it could regulate EPC senescence, proliferation, migration and angiogenesis in an oxidative stress cellular model [33].…”
Section: Discussionsupporting
confidence: 77%
“…Considering that bone marrows are one of the major sources to provide EPCs and enable EPC homing to injured endothelium [30], we supposed that the lower proliferation and migration of EPCs in CAS group manifested the general conditions of the disease, which was similar to the previous ndings in human being [31,32]. Previous clinical ndings suggested that SIRT1 might be protective in CAS patients and in vitro, it could regulate EPC senescence, proliferation, migration and angiogenesis in an oxidative stress cellular model [33].…”
Section: Discussionsupporting
confidence: 77%
“…It has been demonstrated that the increased susceptibility of elderly individuals to ischemic disorders could be mediated, at least in part, by a blunted response of senescent EPCs to hypoxia, which fail to upregulate selected genes related to HIF-1 signaling and glucose uptake (Wu et al, 2018). To this regard, the upregulation of SIRT1 and NRF2 have both been shown to delay EPC senescence and to preserve the proliferative, migratory, and angiogenic activities in senescent EPCs (Lamichane et al, 2019;Wang et al, 2019).…”
Section: Metabolic Features Of Endothelial Cellsmentioning
confidence: 99%
“…MHY2233 is another potent Sirt1 activator; it has been proposed to delay the aging process by decreasing senescence-associated β-galactosidase activity and cellular senescence biomarkers. MHY2233 can improve the proliferation, migration, and overall function of EPCs, which is a primary potential strategy in treating cardiovascular disease [144].…”
Section: Sirt1 Activator Modulates Vascular Disease In Preclinical Anmentioning
confidence: 99%